2015
DOI: 10.4055/cios.2015.7.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Surgical Complications and Learning Curve Associated with Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Single-Institute Experience

Abstract: BackgroundAs surgical complications tend to occur more frequently in the beginning stages of a surgeon's career, knowledge of perioperative complications is important to perform a safe procedure, especially if the surgeon is a novice. We sought to identify and describe perioperative complications and their management in connection with minimally invasive transforaminal lumbar interbody fusion (TLIF).MethodsWe performed a retrospective chart review of our first 124 patients who underwent minimally invasive TLIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Cited factors for nonadoption of MIS techniques include technical factors, limited training opportunities, and increased radiation exposure [74]. Specifically, the lack of training opportunities can lead to a steep learning curve, where earlier cases in a surgeon's experience may be associated with worse operative and clinical outcomes [75][76][77]. Studies investigating the learning curve in MIS techniques have identified earlier cases to be associated with increased operative times, radiation exposure, and complication risk [76][77][78].…”
Section: Limitations To Mis Utilization: the Learning Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Cited factors for nonadoption of MIS techniques include technical factors, limited training opportunities, and increased radiation exposure [74]. Specifically, the lack of training opportunities can lead to a steep learning curve, where earlier cases in a surgeon's experience may be associated with worse operative and clinical outcomes [75][76][77]. Studies investigating the learning curve in MIS techniques have identified earlier cases to be associated with increased operative times, radiation exposure, and complication risk [76][77][78].…”
Section: Limitations To Mis Utilization: the Learning Curvementioning
confidence: 99%
“…Specifically, the lack of training opportunities can lead to a steep learning curve, where earlier cases in a surgeon's experience may be associated with worse operative and clinical outcomes [75][76][77]. Studies investigating the learning curve in MIS techniques have identified earlier cases to be associated with increased operative times, radiation exposure, and complication risk [76][77][78]. Sclafani et al, in a meta-analyis of 15 studies investigating learning curves, determined that 20-30 cases were required to overcome the learning curve for MIS procedures [75].…”
Section: Limitations To Mis Utilization: the Learning Curvementioning
confidence: 99%
“…In the intraoperative phase, impeccable surgical aseptic technique, the timing and selection of antibiotic prophylaxis, and minimizing blood transfusions are key processes. 60,65,66,89,102,144 In the postoperative phase, aseptic wound care and early detection of wound inflammation or breakdown contribute to prevention of delayed contamination and subsequent infection.…”
Section: Rationalementioning
confidence: 99%
“…9 Improvements in disability scores following spine surgery have been demonstrated in a number of conditions. 102,[106][107][108]122,150,151 One multicenter study investigated the outcomes of treatment for lumbar spinal stenosis, which represents the most common indication for surgery in patients over 65 years old. 151 In an as-treated analysis of 654 patients with 4-year follow-up, functional disability was found to be significantly reduced in patients who underwent surgery compared to those treated without surgery.…”
Section: Rationalementioning
confidence: 99%
“…11 Likewise, longer surgical times have been reported for MI, at least during the first cases, which could be a reflection of technical differences, but some authors associate this with a significant learning curve. [12][13][14][15][16][17][18] The objective of this study was to present and analyze the single level MI-TLIF learning curve for a single neurosurgeon (JASS). To this end, we evaluated various parameters, such as surgical time, amount of bleeding, and days of hospitalization.…”
Section: Introductionmentioning
confidence: 99%